Tri Hita Karana: Mediating Work-Life Balance to Enhance Employee Performance at Mandiri Finance - Dwi Oka Lestari Kharisma; Sarwo Edy Handoyo; Andi Harmoko Arifin (Jurnal Ekonomi dan Bisnis Jagaditha, 2025)
Employee performance is a key factor influencing organizational success. To enhance employee performance, it is crucial for management to understand the contributing factors, such as work motivation and employee well-being. This study aims to analyze the impact of work motivation and employee well-being on employee performance, with work-life balance based on Tri Hita Karana as a mediating variable. The research was conducted at Mandiri Finance Denpasar Branch using the Structural Equation Modeling-Partial Least Square (SEM-PLS) method. Data were collected through questionnaires. The results indicate that work motivation positively affects employee performance, as does employee well-being. Additionally, work-life balance based on Tri Hita Karana significantly contributes to improving employee performance. The study also reveals that Tri Hita Karana-based work-life balance mediates the relationship between work motivation and employee performance, as well as the relationship between employee well-being and employee performance. These findings highlight the importance of adopting a Tri Hita Karana-based work-life balance, which emphasizes harmony in relationships with God, fellow humans, and the environment. This approach strengthens the positive effects of work motivation and employee well-being on employee performance.